Levinas, Plotinus reader: inspiring relations - Beltrán Ulate, Esteban Josué (2016)
This study aims to establish a series of ideas about the similarities and disagree- ments between the thought of Plotinus of Lycopolis and Levinas of Kaunas, the challenge becomes apparent from the relationship between the “One” Plotinian and “Infinity” Levinas, in turn, considers the accessibility of human beings, particular entity, the originator point, call it: One or Infinite.